ANALISIS PERTIMBANGAN HAKIM DALAM MEMUTUSKAN PERKARA PIDANA NARKOTIKA YANG DILAKUKAN OLEH ANGGOTA TENTARA NASIONAL INDONESIA PADA PUTUSAN NOMOR 50-K/PM.III-16/AL/IV/2015 DAN PUTUSAN NOMOR 53-K/PM-I-03/AD/IV/2014 - Jeski Wilson; Dian Adriawan DG Tawang (Fakultas Hukum Universitas Tarumanagara, 2020)
This study discusses the Analysis of Judge Considerations in Deciding Narcotics Criminal Cases Conducted by Members of the TNI in Decision Number 50-K / PM.III-16 / AL / IV / 2015 Decision number 53-K / PM-I-03 / AD / IV / 2014. The problem that arises is how the judge's consideration in handling and deciding cases of narcotic crime involving TNI personnel in both cases? Based on the results of the study that the judge in both cases of misuse of narcotics crime by members of the TNI whose case was tried through a military court on case Number: 50-K / PM.III-16 / AL / IV / 2015 with the defendants Tku Agus Slamet and case Number: 53-K / PM-I-03 / AD / IV / 2014 with the accused Sergeant Ismail it can be concluded that the judge's judgment in the criminal prosecution of narcotic offenders refers to the quality and quantity or at least the amount of evidence (narcotics owned or consumed) and look at the time span when the perpetrators consume narcotics (only once without repeating / repeatedly) in a relatively short time.